Contributions of Data Science Educational Paradigm in a Disadvantages Area of Indonesia: a case study - Oviliani Yenty Yuliana; Bernardo Nugroho Yahya; Remuz Maurenz Bertho Kmurawak (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this community service was to disseminate knowledge on Data Science to lecturers and students enrolled in the Information Systems Program Study at Cenderawasih University. Through a webinar series, participants learned about the importance of data science and analytics. This initiative aims to integrate Data Science into the curriculum, which is currently in its final stages. The introduction of a Data Science course expects to enhance the competencies of human resources in Papua, supporting the developmental efforts of the Indonesian Government. Feedback from participants indicates their satisfaction with the speakers, fulfillment of expectations, and acquisition of new knowledge. Considering their input, the upcoming activity will organize as a workshop.